2018
DOI: 10.1109/led.2018.2854733
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Plasmonic UV Detector, Based on Reduced Graphene Oxide/Ag Nanoparticles

Abstract: We report a plasmonic self-powered UV detector based on triboelectric nanogenerators, for the first time. The proposed structure benefits from plasmon-assisted photoresponse in reduced graphene oxide/Ag nanoparticles heterostructure, serving as a high sensitive photoconductive layer in the fabricated triboelectric nanogenerator. Ag nanoparticles enhance the contacting surface area of the triboelectric nanogenerator, and improve the output open circuit voltage by a factor of about 5. The presented triboelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…LSPR refers to the interaction of electromagnetic waves that are confined on metallic nanostructures during illumination and that are sensitive to the refractive index changes around the metallic structure [ 70 ]. It is also applicable for self-powering photoelectronic applications with a broad spectrum of light [ 71 , 72 , 73 ]. A graphene coating with plasmonic has been used extensively due to its superior optical, mechanical and electrical properties, such as high electron mobility, high surface to volume ratio and stable atomic structure [ 45 ].…”
Section: Plasmonic Implementation In Photodetectormentioning
confidence: 99%
See 1 more Smart Citation
“…LSPR refers to the interaction of electromagnetic waves that are confined on metallic nanostructures during illumination and that are sensitive to the refractive index changes around the metallic structure [ 70 ]. It is also applicable for self-powering photoelectronic applications with a broad spectrum of light [ 71 , 72 , 73 ]. A graphene coating with plasmonic has been used extensively due to its superior optical, mechanical and electrical properties, such as high electron mobility, high surface to volume ratio and stable atomic structure [ 45 ].…”
Section: Plasmonic Implementation In Photodetectormentioning
confidence: 99%
“…Au NPs with enhanced photoresponse properties in this device contributed to interband transition in the UV region and LSPR in the visible region. In contrast, a plasmonic self-powered ultraviolet photodetector that applied rGO/Ag NPs was reported in 2018 [ 73 ]. However, this device is based on triboelectric nanogenerators (TENG).…”
Section: Plasmonic Implementation In Photodetectormentioning
confidence: 99%
“…Significant development has been reported regarding the synthesis and application of Ag/rGO [45]. Hence, Keshvari et al [46] reported a triboelectric nanogenerator that works as an active self-powered UV detector with enhanced contact surface area owing to the plasmon-assisted photoresponse in reduced graphene-Ag nanoparticles heterostructure. Paria et al [10] synthesized graphene sheets decorated by silver nanoparticles, forming plasmonic graphene-Silver hybrid composites for a sensitive photodetector, demonstrating a 3.2 AW −1 plasmon photoresponse enhancement in the wavelength range from 330 to 450 nm.…”
Section: Introductionmentioning
confidence: 99%